Application of the Deer Hunting Game in Basketball Learning to Improve Bounce Pass Accuracy Capability at SDN Cipageran Mandiri II - Patricia, Mega Viona; Lengkana, Anggi Setia; Mulyanto, Respaty (Universitas Majalengka, 2024)
This research aims to improve students' accuracy skills in performing basic bounce pass technical movements through the traditional game of deer hunting. This research was carried out at SDN Cipageran Mandiri II in the PJOK subject, with the research subjects being class III-A students for the 2023/2024 academic year, with 30 students consisting of 14 boys and 16 girls. The research method used is Classroom Action Research with a research design using the Kemmis and McTaggart model, which focuses on continuous reflection and action cycles. This classroom action research includes planning, implementing actions, monitoring, evaluating, analyzing, and reflecting. Data was collected at the monitoring and evaluation stage using student activity observation sheets and teacher activity sheets. Then, the data was analyzed both quantitatively and qualitatively. The results of the first research cycle obtained a completeness score of 50%, or as many as 15 people had completed it. In cycle II, there was a completeness score of 86%, or as many as 26 people had finished it. Meanwhile, in cycle III, 100% or 30 people had reached completion. This shows that the actions teachers and students took in the first, second, and third cycles can be said to have completed learning. Based on the results above, deer hunting games can improve bounce pass accuracy results.